Analisa Gender: Peran Ganda Perempuan Sebagai Kepala Keluarga di Tinjau dari Manajemen Pendidikan Islam - Azlina, Nur (STKIP Pesisir Selatan, 2024)
There are several factors that cause these housewives to work. Especially for women as the head of the family. This factor is because her husband does not carry out the function of head of the family due to polygamy, unemployment, illness, job loss, husband leaving for a long time without providing income, divorce and even death. This research is motivated by the dual role of single parent women in Berancah Village as the head of the family who must be smart in dividing time between family, work, and as a member of the community. This research uses a descriptive qualitative approach. The data collection techniques used by researchers include observation, interviews, documentation studies, and literature studies. The findings of the research revealed that the economy is one of the branches of factors that influence women to take on multiple roles (work). In addition, the factors that cause a woman's dual role as head of the family are self-existence, social factors and cultural factors. Based on these four factors, a dual role becomes inherent in a woman in a family. the management strategy of a woman's dual role as head of the family in the perspective of Islamic education management is through leadership, motivation, and communication